Terceros molares mandibulares incluidos e impactados en la población de américa latina: revisión sistemática - Guevara Jaramillo, Yuliana Doménica (2025)
The research focused on impacted and included mandibular third molars in Latin American population through a systematic review. The prevalence and disposition of these molars were identified, using the Pell & Gregory and Winter classifications to assess the complexity of their surgical extraction. Objective: To determine the position and characteristics of impacted and included mandibular third molars in Latin America, and their clinical implications, by analyzing studies published between 2018 and 2024. Materials and Methods: A systematic review was carried out using the PRISMA methodology, collecting information from databases such as PubMed, Dialnet and Redalyc. Relevant articles published in the last five years were included, applying inclusion and exclusion criteria to filter the most significant data. Proposal: A teaching guide was designed to identify the position of third molars using the Pell & Gregory and Winter classifications, facilitating diagnosis and treatment to minimize surgical complications. Conclusions: Impacted and retained third molars have a prevalence of 42.2% to 82% in Latin America. The most frequent positions were Class II A and mesioangular. The main surgical complications include injuries to the inferior alveolar nerve and the lingual nerve. The importance of an accurate diagnosis to reduce risks and optimize results is highlighted.